Thermochromic PVC (polyvinyl chloride) polyester fiber netted coating material

By optimizing the ratio of PVC resin and plasticizer, combined with the microencapsulation treatment of temperature-sensitive color-changing pigments, the problems of coating materials in temperature change monitoring and heat resistance are solved, and the stable and visual color change function is achieved. Durability for long-term use.

CN119162841APending Publication Date: 2024-12-20SIJIA NEW MATERIAL (SHANGHAI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411500603.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Traditional PVC polyester fiber mesh coating materials lack intelligent and visual functions in temperature change monitoring, and the light resistance, heat resistance and aging resistance of temperature-sensitive color-distorted pigments are insufficient, and mismatch in processing temperatures leads to failure or damage in color-distorted functions.

Method used

By optimizing the polymerization degree and plasticizer content of PVC resin, reducing the processing temperature, and microencapsulate the temperature-sensitive color-changing pigment, using rosin resin and polyimide as the coating material, forming a physical barrier and enhancing the pigment resistance Thermal properties and mechanical strength, while using tributyl acetyl citrate or epoxy flaxseed oil as plasticizers, improves the heat resistance and UV resistance of the material.

Benefits of technology

Ensure the stability and color change function of the temperature-sensitive color-changing coating material at high temperatures, significantly improve the flexibility and processing fluidity of the material, extend the service life of the pigment, and improve the wear resistance and adhesion of the coating. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005102488200000091
    Figure BDA0005102488200000091
  • Figure BDA0005102488200000101
    Figure BDA0005102488200000101
Patent Text Reader

Abstract

The invention relates to the field of coatings, and particularly discloses a thermochromic PVC polyester fiber sandwich net coating material. The thermochromic PVC polyester fiber sandwich net coating material comprises the following components in parts by weight: 60-80 parts of PVC resin, 5-10 parts of thermochromic pigment, 48-72 parts of a plasticizer and 1-5 parts of a stabilizer, the polymerization degree of the PVC resin is 850-950, and the content of the plasticizer is 80-90 PHR. According to the thermochromic PVC polyester fiber sandwich net coating material, the problems that a conventional thermochromic pigment is poor in heat resistance, and the color changing performance of the conventional thermochromic pigment is prone to being damaged in the plasticizing processing process of a PVC coating are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of coatings, and more specifically, to a thermochromic PVC polyester fiber sandwich coating material. Background Art

[0002] As a multifunctional composite material, PVC polyester fiber mesh coating material has been widely used in key areas such as pool construction, thermal insulation engineering and gas storage tanks due to its excellent waterproofness, aging resistance, chemical corrosion resistance and good mechanical properties. These fields not only require the material to have basic physical and chemical stability, but also put forward higher requirements for its adaptability under specific environmental conditions, especially in the monitoring of temperature changes.

[0003] Although traditional PVC polyester fiber mesh coating materials can meet basic structural and functional requirements, they are obviously insufficient in intelligent and visual monitoring of ambient temperature. In order to make up for this shortcoming, the development of thermochromic PVC polyester fiber mesh coating materials that can display different colors with temperature changes has become a hot topic in industry research. This material can not only intuitively reflect the ambient temperature and improve the efficiency of safety monitoring, but also provide convenience for the maintenance and management of buildings and engineering facilities.

[0004] However, as a special material based on electron transfer organic compounds, the color change of thermochromic pigments depends on temperature-induced electron transfer and molecular structure reconstruction. Although this pigment shows unique advantages in color conversion, its light resistance, heat resistance, aging resistance and other properties are far inferior to traditional pigments. What is particularly critical is that the processing temperature of thermochromic pigments is usually low, controlled between 160-180°C, while the conventional processing plasticizing temperature of PVC coating materials is as high as 180-210°C. This mismatch in processing temperature makes the color-changing function of thermochromic pigments ineffective or damaged at high temperatures. Summary of the invention

[0005] In order to solve the above problems, the present application provides a thermochromic PVC polyester fiber mesh coating material.

[0006] The present application provides a thermochromic PVC polyester fiber mesh coating material using the following technical solutions: A thermochromic PVC polyester fiber sandwich coating material comprises, by weight, 60-80 parts of PVC resin, 5-10 parts of thermochromic pigment, 48-72 parts of plasticizer, and 1-5 parts of stabilizer. The polymerization degree of the PVC resin is 850-950, and the content of the plasticizer is 80-90 PHR.

[0007] By adopting the above technical solution, the present application effectively reduces the processing temperature of PVC by optimizing the degree of polymerization of PVC resin, which is more compatible with the processing temperature of thermochromic pigment, thereby avoiding the degradation of pigment at high temperature and ensuring the stability of color changing function. By increasing the content of plasticizer to 80-90PHR, the flexibility and processing fluidity of PVC material can be significantly improved, so that a good coating effect can still be obtained at a lower processing temperature. The effect of plasticizer reduces the processing temperature of PVC resin and does not affect the coating performance, thereby ensuring the normal performance of its color changing function.

[0008] Optionally, the thermochromic pigment needs to be microencapsulated.

[0009] Optionally, the specific steps of microencapsulation of the thermochromic pigment are: Dissolve rosin resin and polyimide in a solvent at a mass ratio of 1:(2-4) to form a uniform solution; Dispersing the thermochromic pigment into a mixed solution of rosin resin and polyimide, the ratio of the amount of the thermochromic pigment added to the total mass of the rosin resin and polyimide being 1:(1-1.5), and dispersing the mixture evenly by ultrasonication; Gradually add a crosslinking agent to the mixed solution while stirring, the amount of the crosslinking agent is 5-10% of the total mass of the rosin resin and the polyimide, and react at 50-80° C. for 2-4 hours; After the reaction is completed, the reactants are dried in vacuum at 45-55°C to remove the solvent, and the dried product is ground to 20-40 microns to obtain a microencapsulated thermochromic pigment.

[0010] By adopting the above technical scheme, the thermochromic pigment is microencapsulated and rosin resin and polyimide are used as coating materials to form a physical barrier to the pigment. Rosin resin and polyimide themselves have good heat resistance, and the heat resistance of the pigment after microencapsulation is significantly improved. The microencapsulated structure formed under the reaction conditions of 50-80°C can enable the pigment to maintain color reversibility at high temperatures and improve its aging resistance, thereby ensuring the stability of the pigment function during long-term use. The thermochromic pigment is uniformly dispersed in a solution of rosin resin and polyimide by ultrasonic dispersion technology, and then cross-linked so that the pigment is uniformly encapsulated in the microcapsule. The thermochromic pigment after microencapsulation can not only enhance the aging resistance, but also provide additional mechanical strength through the chemical properties of rosin resin and polyimide. In the coating material, the presence of microencapsulated pigments can improve the wear resistance and adhesion of the coating, so that the durability of the coating material in use is significantly enhanced. At the same time, the size of the microencapsulated pigment is controlled at 20-40 microns, making it easier to mix and process in coating materials, further improving the fluidity and processing efficiency of the material.

[0011] Optionally, the rosin resin is hydrogenated rosin resin.

[0012] By adopting the above technical solution, hydrogenated rosin resin removes some double bonds through hydrogenation treatment, thereby significantly improving its antioxidant and aging resistance. Compared with ordinary rosin resin, hydrogenated rosin resin is more stable in the external environment, which prolongs the life of microencapsulated pigments and ensures the stability and durability of thermochromic pigments in long-term applications. At the same time, hydrogenated rosin resin has a high transparency and can maintain the clarity of the coating material during the microencapsulation process. This is especially important for thermochromic pigments, because the higher the transparency of the coating, the more obvious and intuitive the color change effect of the pigment, which helps to achieve clearer and brighter color conversion.

[0013] Optionally, the cross-linking agent includes bisphenol A epoxy resin and hexamethylene diisocyanate compounded in a mass ratio of 8:5.

[0014] By adopting the above technical solution, bisphenol A epoxy resin and HDI undergo cross-linking reaction at the same time to form a double cross-linking network, namely the thermosetting cross-linking of epoxy resin and the polyurethane cross-linking of HDI. Due to its high glass transition temperature and excellent thermal stability, the epoxy cross-linking structure can maintain the integrity of the microcapsule structure under high temperature environment. At the same time, the polyurethane cross-linking structure of HDI also improves the thermal stability of the material, further avoiding degradation under high temperature environment. In addition, the epoxy cross-linking structure has good resistance to acids, alkalis, solvents, etc., while the polyurethane network formed by HDI has higher tolerance to moisture and polar chemicals. The double cross-linking structure combines the advantages of the two materials, making the microcapsule material exhibit stronger chemical corrosion resistance in various chemical environments, ensuring that it is not corroded by external chemicals during long-term use.

[0015] Optionally, the plasticizer is selected from one of acetyl tributyl citrate and epoxy linseed oil.

[0016] By adopting the above technical solution, the molecular structure of acetyl tributyl citrate contains multiple ester groups, which can effectively reduce the glass transition temperature of the polymer. The low volatility and high heat resistance of acetyl tributyl citrate make it stable during the processing and not easy to volatilize or decompose. In addition, acetyl tributyl citrate is a safe and non-toxic plasticizer that does not release harmful substances. Epoxy linseed oil not only has a good plasticizing effect, but its epoxy structure can also improve the heat resistance and UV resistance of the material, reducing the degradation or aging of the coating when exposed to ultraviolet rays or high temperature conditions.

[0017] Optionally, the stabilizer includes 3-4 parts of calcium stearate, 1-2 parts of zinc stearate, 1-2 parts of paraffin oil, 0.05-0.1 parts of 2,6-di-tert-butyl-p-cresol, and 0.2-0.5 parts of ultraviolet absorber.

[0018] By adopting the above technical solutions, calcium stearate and zinc stearate can effectively inhibit the thermal decomposition of materials, improve the heat resistance of thermochromic pigments, and prevent the material from decomposing during high-temperature processing or long-term use. 2,6-di-tert-butyl-p-cresol prevents the oxidative degradation of materials by capturing free radicals, delays the aging process of thermochromic pigments, and increases their service life. Ultraviolet absorbers absorb ultraviolet rays to prevent thermochromic pigments from being photodegraded and prevent their color drift or discoloration. The lubricating effect of paraffin oil improves the fluidity and demoulding properties of the material during processing and reduces processing defects. Through the synergistic effect of multiple components, the stabilizer system improves the comprehensive performance of microencapsulated thermochromic pigments from three aspects: heat, light, and oxygen, ensuring its stability and durability in harsh environments.

[0019] Optionally, the preparation method of the thermochromic PVC polyester fiber sandwich coating material is: Put the PVC resin into a stirring device, add a plasticizer, and mix thoroughly. After mixing, add a thermochromic pigment and a stabilizer, and disperse the mixture through an ultrasonic dispersing device. After the treatment, let the mixture stand for 2-4 hours. After standing, a thermochromic PVC polyester fiber sandwich coating material is obtained.

[0020] By adopting the above technical solution, ultrasonic dispersion can effectively disperse the thermochromic pigment and stabilizer evenly into the PVC matrix, avoiding the aggregation or uneven distribution of the pigment in the coating material, and ensuring the consistent color change effect of the material.

[0021] In summary, this application has the following beneficial effects: 1. Since the present application optimizes the degree of polymerization of PVC resin and reduces the processing temperature, it is more compatible with the processing temperature of thermochromic pigment, avoiding degradation of pigment at high temperature and ensuring the stability of color changing function. At the same time, the plasticizer content is increased to 80-90PHR, which significantly improves the flexibility and processing fluidity of PVC material, so that good coating effect can still be obtained at lower processing temperature. The addition of plasticizer not only reduces the processing temperature of PVC, but also does not affect the performance of coating, ensuring the normal function of color changing function of the material.

[0022] 2. In this application, it is preferred to microencapsulate the thermochromic pigment, use rosin resin and polyimide as coating materials, form a physical barrier to the pigment, significantly improve the heat resistance, aging resistance and mechanical strength of the pigment, and achieve uniform distribution and cross-linking through ultrasonic dispersion technology. The size of the microcapsule is controlled at 20-40 microns, which further improves the mixing and processing efficiency of the pigment in the coating, ensuring the stability and performance of the coating in long-term use.

[0023] 3. The present application preferably uses acetyl tributyl citrate or epoxy linseed oil as a plasticizer, which effectively reduces the glass transition temperature of the polymer, improves the heat resistance and UV resistance of the material, and ensures stability during processing. Acetyl tributyl citrate has low volatility and non-toxicity, while epoxy linseed oil also has good plasticizing and anti-aging effects. The stabilizer system includes calcium stearate, zinc stearate, paraffin oil, 2,6-di-tert-butyl-p-cresol and ultraviolet absorber, which inhibits thermal decomposition, oxidative degradation and ultraviolet damage through synergistic effects, prolongs the service life of the thermochromic pigment, and ensures its stability and durability in harsh environments. DETAILED DESCRIPTION

[0024] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.

[0025] Preparation Example of Microencapsulated Thermochromic Pigment Preparation Example 1 Preparation of microencapsulated thermochromic pigments: 10 kg of first-grade rosin resin (purchased from Jiangxi Huajin New Materials Co., Ltd.) and 30 kg of polyimide (purchased from Mitsui Chemicals PL450C of Japan) were added to sufficient dichloromethane and stirred at 35° C. with a magnetic stirrer until the rosin resin and polyimide were completely dissolved to form a uniform solution.

[0026] The thermochromic pigment adopts BS0001 thermochromic vermilion pigment produced by Dongguan Bianse Chemical Technology Co., Ltd.

[0027] 50 kg of thermochromic pigment was added to the above-formed mixed solution of rosin resin and polyimide, and the solution was treated using an ultrasonic dispersion device. The ultrasonic dispersion time was 30 minutes and the frequency was set at 28 kHz.

[0028] Under stirring, 3.2 kg of crosslinking agent was gradually added to the dispersed solution, wherein the crosslinking agent contained 1.97 kg of bisphenol A epoxy resin and 1.23 kg of hexamethylene diisocyanate, and the amount of the crosslinking agent was 8% of the total mass of the rosin resin and the polyimide. After the crosslinking agent was added, the reaction was continued at a constant temperature of 65° C. for 3 hours.

[0029] After the reaction is completed, the reactants are placed in a vacuum drying oven and dried at 50°C until all the solvents are evaporated. The dried product is a lump-like substance, which is ground into a particle size of 30±10 microns by a ball mill. After grinding, a microencapsulated thermochromic pigment is obtained.

[0030] Preparation Example 2 Preparation of microencapsulated thermochromic pigment: The difference from Preparation Example 1 is that 10 kg of rosin resin, 20 kg of polyimide, 37.5 kg of thermochromic pigment, and 2.4 kg of cross-linking agent are used.

[0031] Preparation Example 3 Preparation of microencapsulated thermochromic pigment: The difference from Preparation Example 1 is that 10 kg of rosin resin, 40 kg of polyimide, 62.5 kg of thermochromic pigment and 4 kg of cross-linking agent are used.

[0032] Preparation Example 4 Preparation of microencapsulated thermochromic pigments: The difference from Preparation Example 1 is that the rosin resin uses first-grade highly hydrogenated rosin (purchased from Guangxi Wuzhou Richeng Forest Products Chemical Co., Ltd.).

[0033] Preparation Example 5 Preparation of microencapsulated thermochromic pigment: The difference from Preparation Example 1 is that 40 kg of first-grade rosin resin is used as the microencapsulated coating material.

[0034] Preparation Example 6 Preparation of microencapsulated thermochromic pigment: The difference from Preparation Example 1 is that 40 kg of polyimide is used as the microencapsulated coating material.

[0035] Preparation Example 7 Preparation of microencapsulated thermochromic pigment: The difference from Preparation Example 1 is that the cross-linking agent contains 1.72 kg of bisphenol A epoxy resin and 1.48 kg of hexamethylene diisocyanate.

[0036] Preparation Example 8 Preparation of microencapsulated thermochromic pigment: The difference from Preparation Example 1 is that the cross-linking agent contains 2.22 kg of bisphenol A epoxy resin and 0.98 kg of hexamethylene diisocyanate.

[0037] Preparation example of stabilizer Preparation Example 9 Preparation of stabilizer: Prepare 3.5 kg of calcium stearate, 1.5 kg of zinc stearate, 1.5 kg of paraffin oil, 0.08 kg of 2,6-di-tert-butyl-p-cresol, and 0.4 kg of UV531 ultraviolet absorber. All of the above raw materials are purchased from Merck Reagents.

[0038] In a dry and clean reactor, first add calcium stearate and zinc stearate, start the agitator at room temperature for preliminary mixing at a stirring speed of 250 rpm, then add paraffin oil to the mixture and continue stirring for 15 minutes until a uniform paste is obtained.

[0039] The stirring speed was reduced to 100 rpm, and 2,6-di-tert-butyl-p-cresol and the ultraviolet absorber were added, and the stirring time was 10 minutes.

[0040] After all components are evenly mixed, the temperature of the reactor is gradually raised to 80°C and kept warm. After stirring for 30 minutes, the heating is stopped and the mixture is gradually cooled to room temperature. Stirring is maintained during this period to prevent the material from stratification or precipitation. After cooling, a stabilizer is obtained.

[0041] Preparation Example 10 Preparation of stabilizer: The difference from Preparation Example 9 is that 3 kg of calcium stearate, 1 kg of zinc stearate, 1 kg of paraffin oil, 0.05 kg of 2,6-di-tert-butyl-p-cresol, and 0.2 kg of UV531 ultraviolet absorber were prepared.

[0042] Preparation Example 11 Preparation of stabilizer: The difference from Preparation Example 9 is that 4 kg of calcium stearate, 2 kg of zinc stearate, 2 kg of paraffin oil, 0.1 kg of 2,6-di-tert-butyl-p-cresol, and 0.5 kg of UV531 ultraviolet absorber were prepared. Example

[0043] Example 1 A preparation method of a thermochromic PVC polyester fiber sandwich coating material: 70 kg of PVC resin with a degree of polymerization of 900 was added to the mixer, and 59.5 kg of acetyl tributyl citrate plasticizer (purchased from Merck Reagent, model 388378) was added, with a plasticizer content of 85 PHR. Preliminary mixing was performed at 200 r / min, and the stirring time was set to 10 minutes to ensure that the two were fully mixed.

[0044] The thermochromic pigment in this application adopts BS0001 thermochromic vermilion pigment produced by Dongguan Bianse Chemical Technology Co., Ltd.

[0045] 8 kg of thermochromic pigment and 3 kg of stabilizer were slowly added. The stabilizer was prepared in Preparation Example 9. The mixture was stirred at a speed of 100 r / min to avoid agglomeration of the pigment. The stirring time was 10 minutes.

[0046] After stirring, the mixture was transferred to an ultrasonic dispersion device, and the ultrasonic frequency was set to 30 kHz and the treatment time was 15 minutes. During the dispersion process, the temperature was controlled at 50°C to help enhance the fluidity of the material and prevent bubbles from forming in the mixture during ultrasonic treatment.

[0047] After the ultrasonic dispersion was completed, the mixture was placed in a sealed container and allowed to stand at room temperature for 3 hours to obtain a coating material.

[0048] Example 2 A method for preparing a thermochromic PVC polyester fiber sandwich coating material: the difference from Example 1 is that 60 kg of PVC resin, 5 kg of thermochromic pigment, 51 kg of plasticizer, and 1 kg of stabilizer are selected.

[0049] Example 3 A method for preparing a thermochromic PVC polyester fiber sandwich coating material: the difference from Example 1 is that 80 kg of PVC resin, 10 kg of thermochromic pigment, 68 kg of plasticizer, and 5 kg of stabilizer are selected.

[0050] Example 4 A method for preparing a thermochromic PVC polyester fiber sandwich coating material: the difference from Example 1 is that 56 kg of acetyl tributyl citrate plasticizer is added, and the plasticizer content is 80 PHR.

[0051] Example 5 A method for preparing a thermochromic PVC polyester fiber sandwich coating material: the difference from Example 1 is that 63 kg of acetyl tributyl citrate plasticizer is added, and the plasticizer content is 90 PHR.

[0052] Example 6 A method for preparing a thermochromic PVC polyester fiber sandwich coating material: the difference from Example 1 is that the degree of polymerization of the PVC resin is 850.

[0053] Example 7 A method for preparing a thermochromic PVC polyester fiber sandwich coating material: the difference from Example 1 is that the degree of polymerization of the PVC resin is 900.

[0054] Example 8 A method for preparing a thermochromic PVC polyester fiber sandwich coating material: The difference from Example 1 is that the plasticizer is epoxy linseed oil purchased from Maclean Reagent, model E762810.

[0055] Example 9 A method for preparing a thermochromic PVC polyester fiber sandwich coating material: the difference from Example 1 is that the stabilizer is prepared by Preparation Example 10.

[0056] Example 10 A method for preparing a thermochromic PVC polyester fiber sandwich coating material: the difference from Example 1 is that the stabilizer is prepared by Preparation Example 11.

[0057] Embodiment 11 A method for preparing a thermochromic PVC polyester fiber sandwich coating material: The difference from Example 1 is that the thermochromic pigment is the microencapsulated thermochromic pigment prepared in Preparation Example 1.

[0058] Example 12 A method for preparing a thermochromic PVC polyester fiber sandwich coating material: The difference from Example 11 is that the thermochromic pigment is the microencapsulated thermochromic pigment prepared in Preparation Example 2.

[0059] Embodiment 13 A method for preparing a thermochromic PVC polyester fiber sandwich coating material: The difference from Example 11 is that the thermochromic pigment is the microencapsulated thermochromic pigment prepared in Preparation Example 3.

[0060] Embodiment 14 A method for preparing a thermochromic PVC polyester fiber sandwich coating material: The difference from Example 11 is that the thermochromic pigment is the microencapsulated thermochromic pigment prepared in Preparation Example 4.

[0061] Comparative Example Comparative Example 1 A method for preparing a thermochromic PVC polyester fiber sandwich coating material: the difference from Example 1 is that the degree of polymerization of the PVC resin is 1000.

[0062] Comparative Example 2 A method for preparing a thermochromic PVC polyester fiber sandwich coating material: the difference from Example 1 is that the degree of polymerization of the PVC resin is 800.

[0063] Comparative Example 3 A method for preparing a thermochromic PVC polyester fiber sandwich coating material: the difference from Example 1 is that the plasticizer content is 100 PHR.

[0064] Comparative Example 4 A method for preparing a thermochromic PVC polyester fiber sandwich coating material: the difference from Example 1 is that the plasticizer content is 70 PHR.

[0065] Comparative Example 5 A method for preparing a thermochromic PVC polyester fiber sandwich coating material: The difference from Example 11 is that the thermochromic pigment is the microencapsulated thermochromic pigment prepared in Preparation Example 5.

[0066] Comparative Example 6 A method for preparing a thermochromic PVC polyester fiber sandwich coating material: The difference from Example 11 is that the thermochromic pigment is the microencapsulated thermochromic pigment prepared in Preparation Example 6.

[0067] Comparative Example 7 A method for preparing a thermochromic PVC polyester fiber sandwich coating material: The difference from Example 11 is that the thermochromic pigment is the microencapsulated thermochromic pigment prepared in Preparation Example 7.

[0068] Comparative Example 8 A method for preparing a thermochromic PVC polyester fiber sandwich coating material: The difference from Example 11 is that the thermochromic pigment is the microencapsulated thermochromic pigment prepared in Preparation Example 8.

[0069] Performance testing Detection Methods Use polyester fiber mesh as the substrate, keep the surface clean and dry, and the mesh aperture is 2 mm. Use the scraping method to apply the PVC mixture after standing on the fiber mesh. The scraping thickness is controlled between 0.2 mm to ensure that the coating can evenly cover the surface of the mesh.

[0070] After coating, the mesh cloth coated with the PVC mixture was thermoformed at 140°C, 160°C, 180°C, and 200°C, respectively. After completion, its hardness after curing was tested, and a colorimeter was used to test the color difference ΔE when the temperature was raised from room temperature of 30°C to 60°C.

[0071] Table 1 Test data statistics It can be seen from Example 1, Example 4-7 and Comparative Examples 1-4 and Table 1 that when the degree of polymerization of PVC is about 900, the molecular chain is short and the intermolecular force is relatively weak, which enables the material to melt at a lower temperature during processing, thereby reducing the processing temperature and avoiding the degradation of the thermochromic pigment under high temperature conditions. As the content of plasticizer increases, the plasticizing temperature continues to decrease. The role of the plasticizer is to reduce the glass transition temperature and melting temperature of PVC, thereby improving processability. When the content of plasticizer is 80-90PHR, the plasticizing temperature is ideal, which not only meets the low temperature plasticizing requirements, but also ensures the stability of the thermochromic pigment. Experiments have verified that when the degree of polymerization of PVC is about 900 and the total content of plasticizer is 80-90PHR, the use of a low-temperature plasticizer can ensure that PVC is molded at a lower plasticizing temperature, and the color change performance of the pigment and the curing molding effect are not affected.

[0072] It can be seen from Example 9 and Comparative Examples 5-8 and Table 1 that bisphenol A epoxy resin and HDI undergo crosslinking reaction simultaneously to form a double crosslinking network, namely, the thermosetting crosslinking of epoxy resin and the polyurethane crosslinking of HDI. The epoxy crosslinking structure can maintain the integrity of the microcapsule structure under high temperature environment due to its high glass transition temperature and excellent thermal stability. At the same time, the polyurethane crosslinking structure of HDI also improves the thermal stability of the material, further avoiding degradation under high temperature environment. The specific mass ratio of 1: (2-4) is to give full play to the synergistic effect of rosin resin and polyimide, maintain good film forming property and fluidity in the coating layer, and provide high temperature tolerance and strength. Compared with using it alone, the effect after compounding is more excellent, which can significantly improve the heat resistance, aging resistance and coating performance of the pigment, while not affecting its processing and handling performance. This compounding strategy ensures the long-term stability and functionality of the thermochromic pigment in high temperature application scenarios.

[0073] It can be seen from Examples 1-3 and Table 1 that by optimizing the degree of polymerization of the PVC resin, the processing temperature is reduced, making it more compatible with the processing temperature of the thermochromic pigment, avoiding degradation of the pigment at high temperatures, and ensuring the stability of the color-changing function. At the same time, the plasticizer content is increased to 80-90 PHR, which significantly improves the flexibility and processing fluidity of the PVC material, so that a good coating effect can still be obtained at a lower processing temperature. The addition of the plasticizer not only reduces the processing temperature of the PVC, but also does not affect the performance of the coating, ensuring that the color change function of the material is performed normally. The addition of the stabilizer is to improve the heat resistance of the material, prevent PVC from degrading, and enhance the weather resistance and heat resistance of the material.

[0074] It can be seen from Examples 1 and 8 and Table 1 that the use of acetyl tributyl citrate or epoxy linseed oil as a plasticizer can effectively reduce the glass transition temperature of the polymer, improve the heat resistance of the material, and ensure stability during processing.

[0075] It can be seen from Example 1 and Examples 9-10 and Table 1 that the stabilizer system improves the comprehensive performance of the microencapsulated thermochromic pigment through the synergistic effect of multiple components, ensuring its stability and durability in harsh environments.

[0076] It can be seen from Example 1 and Examples 11-14 and Table 1 that the thermochromic pigment is microencapsulated and a physical barrier is formed for the pigment using rosin resin and polyimide as coating materials, which significantly improves the heat resistance of the pigment. The hydrogenated rosin resin is hydrogenated to remove some double bonds, thereby significantly improving its oxidation resistance and aging resistance. Compared with ordinary rosin resin, hydrogenated rosin resin is more stable in the external environment, which prolongs the life of the microencapsulated pigment and ensures the stability and durability of the thermochromic pigment in long-term applications.

[0077] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A thermochromic PVC polyester fiber mesh coating material, characterized in that: The components thereof include 60-80 parts of PVC resin, 5-10 parts of thermochromic pigment, 48-72 parts of plasticizer and 1-5 parts of stabilizer by weight. The polymerization degree of the PVC resin is 850-950, and the content of the plasticizer is 80-90 PHR.

2. The thermochromic PVC polyester fiber mesh coating material according to claim 1, characterized in that: The thermochromic pigment needs to be microencapsulated.

3. The thermochromic PVC polyester fiber mesh coating material according to claim 2, characterized in that: The specific steps of the thermochromic pigment microencapsulation process are: Dissolve rosin resin and polyimide in a solvent at a mass ratio of 1:(2-4) to form a uniform solution; Dispersing the thermochromic pigment into a mixed solution of rosin resin and polyimide, the ratio of the amount of the thermochromic pigment added to the total mass of the rosin resin and polyimide being 1:(1-1.5), and dispersing the mixture evenly by ultrasonication; Gradually add a crosslinking agent to the mixed solution while stirring, the amount of the crosslinking agent is 5-10% of the total mass of the rosin resin and the polyimide, and react at 50-80°C for 2-4 hours; After the reaction is completed, the reactants are dried in vacuum at 45-55°C to remove the solvent, and the dried product is ground to 20-40 microns to obtain a microencapsulated thermochromic pigment.

4. The thermochromic PVC polyester fiber mesh coating material according to claim 3, characterized in that: The rosin resin is hydrogenated rosin resin.

5. The thermochromic PVC polyester fiber mesh coating material according to claim 3, characterized in that: The cross-linking agent includes bisphenol A epoxy resin and hexamethylene diisocyanate compounded in a mass ratio of 8:

5.

6. The thermochromic PVC polyester fiber mesh coating material according to claim 1, characterized in that: The plasticizer is selected from one of acetyl tributyl citrate and epoxy linseed oil.

7. The thermochromic PVC polyester fiber mesh coating material according to claim 1, characterized in that: The stabilizer comprises 3-4 parts of calcium stearate, 1-2 parts of zinc stearate, 1-2 parts of paraffin oil, 0.05-0.1 parts of 2,6-di-tert-butyl-p-cresol, and 0.2-0.5 parts of ultraviolet absorber.

8. The thermochromic PVC polyester fiber mesh coating material according to claim 1, characterized in that: The preparation method of the thermochromic PVC polyester fiber sandwich coating material is as follows: Put the PVC resin into a stirring device, add a plasticizer, and mix thoroughly. After mixing, add a thermochromic pigment and a stabilizer, and disperse the mixture through an ultrasonic dispersing device. After the treatment, let the mixture stand for 2-4 hours. After standing, a thermochromic PVC polyester fiber sandwich coating material is obtained.